2021
DOI: 10.1177/15248399211027540
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ Perceptions of Health Care Providers’ Dismissive Communication

Abstract: Some patients experience negative interactions with health care providers, such as when they perceive that their concerns are ignored by providers. The present study, guided by patient-centered communication, examined health care provider communication behaviors that resulted in patients feeling dismissed, and whether there were differences in providers who dismissed being perceived as (dis)similar to the patients in gender, race/ethnicity, or age. U.S. adults claiming they felt dismissed by a provider were as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…As a result, this study offers further avenues to explore narrative-based resilience scholarship in the face of disruptive life events (Betts et al, 2022), like chronic illness (Venetis et al, 2020). Finally, this study contributes to a growing body of communication scholarship on autoimmune disease (Castle & Koenig Kellas, 2019; Gunning, 2022; Thompson, Pulido, et al, 2022) and dismissive and disenfranchising experiences for individuals with chronic illness and pain (Gunning & Taladay-Carter, 2023; Hildenbrand et al, 2022; Hintz & Tucker, 2023), notably women (Hintz, 2022; Thompson, Babu, & Makos, 2022, 2023).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…As a result, this study offers further avenues to explore narrative-based resilience scholarship in the face of disruptive life events (Betts et al, 2022), like chronic illness (Venetis et al, 2020). Finally, this study contributes to a growing body of communication scholarship on autoimmune disease (Castle & Koenig Kellas, 2019; Gunning, 2022; Thompson, Pulido, et al, 2022) and dismissive and disenfranchising experiences for individuals with chronic illness and pain (Gunning & Taladay-Carter, 2023; Hildenbrand et al, 2022; Hintz & Tucker, 2023), notably women (Hintz, 2022; Thompson, Babu, & Makos, 2022, 2023).…”
Section: Discussionmentioning
confidence: 85%
“…As a result, emerging adults experiencing the onset of chronic illness symptoms struggle to find stories like theirs, resulting in mental health and identity impacts, including depression, anxiety, and fear for the future (Wilson & Stock, 2019). Due to their age, patients may experience contestation , or disbelief, of their symptoms by healthcare providers (Bontempo, 2022; Hildenbrand et al, 2022) and relational others (e.g., family members, friends; Hintz & Wilson, 2021; Thompson & Duerringer, 2020; Thompson et al, 2023), being told that they are too young to be sick (Gunning, 2022). As a result of contestation and a lack of stories that mirror their own experiences, emerging adults with chronic illness grapple with cognitive dissonance as they compare their former “well” selves to their new “ill” or “abnormal” identities, alongside their “normal” peers and relational others (April et al, 2021; Wilson & Stock, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extending research on communication interactions in the context of chronic, invisible, and contested illness adds nuance to interpersonal interactions to provide better support for patients and their loved ones. The present study builds upon disenfranchising (Hintz, 2022; Thompson et al, 2022) and dismissive communication research, like Hildenbrand et al’s (2022) study which identified HCP actions that patients perceive as dismissive, by identifying the specific, interpersonally and verbally communicated messages that patients perceive as dismissive and (non)supportive. Identifying specific language offers a guidebook for HCPs and relational others to effectively communicate support to individuals navigating illness and pain.…”
Section: Discussionmentioning
confidence: 99%
“…Hedegaard (2019) studied medical personnel interacting with patients and found that when patients did not follow stereotypically gendered norms, the staff interacted differently with them (more informally, less "professionally"). Hildenbrand, Perrault, and Rnoh (2022) found that female patients were more likely to feel they were treated dismissively by healthcare providers than male patients. Mavisakalyan's (2015) meta-analysis of previous research on gender differentiation in languages around the world (such as gendered nouns or pronouns) showed a relationship with women's labor force participation.…”
Section: Literature Review Gender/ing Language and Communicationmentioning
confidence: 96%